The Impact of COVID-19 Pandemic on Children’s Lives - Alsaadi, Asma; Alomosh, Ahmad (Al-Adab Journal, 2024)
This study suggests remedies for the negative effect of the Coronavirus (COVID-19) pandemic on the lives of children. It aims to determine the extent to which the children’s social lives, behavior, and cultures have been affected by the pandemic and propose appropriate plans and solutions to help them return to the lives they were accustomed to before the pandemic. This study’s problem is linked to the adverse effects on children resulting from preventive measures applied to stop the spread of the virus, including social distancing, closing schools and other facilities, and introducing quarantines. Despite the reality that these measures were aimed at protecting communities, they have affected children’s psychological and social health and educational and cultural lives. On the other hand, violence against children has significantly increased, as studies conducted in various countries have concluded. This study is crucial because it draws attention to the impact of the Covid-19 pandemic on children’s lives, as these children are the future leaders. It concludes that most children worldwide have been affected since the beginning of the COVID-19 pandemic, with the impact differing based on culture, family, cultural, and economic components. The study’s recommendations attempt to encourage the implementation of plans that match the age groups of children to deal with the effects of the COVID-19 pandemic before these children return to everyday life so as not to be shocked when they discover that things have changed for good.